Adoption in Polar Bears (Ursus maritimus) ... - Derocher, A.E.; Wiig, Ø. (University of Alberta Library, 1999)
We observed a case of adoption of a single four-month-old polar bear cub (Ursus maritimus) into an existing litter of two cubs on Hopen Island, Svalbard. We believe the high density of maternity dens in the study area may increase the likelihood of natural adoption. Speculation about theoretical implications of adoption is of scientific interest. However, we believe that the probability of adoption may increase when family groups are captured, and the scientific interpretation of such events is of questionable value. We urge researchers to exercise caution in handling family groups in high-density den areas. ...